A review on the research status and development trend of equipment in water treatment processes of recirculating aquaculture systems. (8th July 2018) - Xiao, Ruichao; Wei, Yaoguang; An, Dong; Li, Daoliang; Ta, Xuxiang; Wu, Yinghao; Ren, Qin
Abstract: Recirculating aquaculture systems (RASs) are intensive aquaculture facilities models that depend on diverse water treatment equipment to maintain good water quality and produce safe and healthy high‐quality aquatic products. This article combines the main farming‐mode of water purification recirculating processes with recent cultivation‐mode scientific research and the current development of the recirculating aquaculture industry. Harmful substances are present in aquaculture wastewater due to large quantities of residual particulate matter such as residual feed, faeces and small suspended solid particles, as well as ammonia, nitrite, bacteria and carbon dioxide (CO2 ), in the water. These harmful substances seriously affect the quality of aquatic products, so water treatment equipment is needed to remove these substances, add oxygen (O2 ) to the water and adjust the temperature of the water to ensure a high‐quality environment for fish survival. This article reviews the equipment for physical filtration (e.g. solid–liquid separation equipment, microscreen drum filter and foam fractionator) that could remove suspended solids during the water treatment of RASs and the equipment for biological filtration (e.g. fluidized sand biofilter (FSB), moving‐bed biofilm reactor (MBBR) and rotating biological contactor (RBC)) that could remove ammonia nitrogen, nitrite and other hazardous substances from wastewater, as well as equipment for water disinfection and sterilization, O2 addition, CO2 removal and temperature control. Comprehensive analysis and discussion of water treatment efficiency are provided for reference to create efficient high‐end recirculation aquaculture models and increase the precision and intelligence degree of recirculating water treatment technologies in the future.